LEARNING AMID CRISIS: EFL STUDENTS’ PERCEPTION ON ONLINE LEARNING DURING COVID-19 OUTBREAK - Kasyfur Rahman (ETERNAL (English, Teaching, Learning and Research Journal), 2020)
This paper investigated tertiary EFL students’ overall perception of the use of fully online learning during the Covid-19 pandemic. By administering a survey to 125 students of the English Language Education Program in a State Islamic University in West Nusa Tenggara, Indonesia, using 26 items of a questionnaire with a five-point Likert scale, this study unravelled students’ responses in terms of three constructs including Perceived Usefulness (PU), Perceived Ease of Use (PEOU) and Perceived Instructor Characteristics (PIC). The findings suggested that in terms of PU, even though the data mostly demonstrated neutral responses for most of the questionnaire items, the students tended to perceive online learning as to provide flexible time for their learning and foster their autonomy/independence and confidence. However, the students tended to perceive online learning as less facilitating for their understanding of subjects. In terms of PEOU, the responses reflected the students’ readiness to employ online learning as the data suggested that they possessed both the technology and the knowledge to use it. However, they tended to encounter problems when operating the technology, especially concerning the internet connection. On the other hand, these students perceived instructor characteristics as mostly positive. Therefore, online learning seemed to have not been designed to engage all students, yet seemed to be an inevitable option during the outbreak as the report from the interviews demonstrated that F2F classes were still preferred over online learning. Finally, these findings imply the need for redesigning online learning to better engage students in virtual classes.